Proceedings of the 10th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2018
DOI: 10.1145/3239060.3239063
|View full text |Cite
|
Sign up to set email alerts
|

Why Disable the Autopilot?

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…However, they might be useful as they are simple and fast to collect data. For instance, some studies just let participants leave any comment they wish after the experiment (𝑛 = 2) or opt for a open-ended question (𝑛 = 3) (i.e., what-how-why questions) to study participants' general attitude to AI [107], to understand participants' decision-making [219], and to directly investigate participants' trust [71].…”
Section: Nonmentioning
confidence: 99%
“…However, they might be useful as they are simple and fast to collect data. For instance, some studies just let participants leave any comment they wish after the experiment (𝑛 = 2) or opt for a open-ended question (𝑛 = 3) (i.e., what-how-why questions) to study participants' general attitude to AI [107], to understand participants' decision-making [219], and to directly investigate participants' trust [71].…”
Section: Nonmentioning
confidence: 99%
“…To provide additional context to these PAMs, we provide examples of each in commercial video games, but did not attempt to systematically review that space. [4] extra shield Bateman et al [5] sticky targets, target gravity cursor area (+) Cechanowicz [7] speed (+), steering acceleration (+) (virtual car) Depping et al [10] outgoing incoming bullet magnetism damage (+) damage (-) Gerling et al [14] score (+) on hit perfect score timing van Huysduynen [16] autopilot (driving sim) Hunicke [18] extra health when low Jensen, Grønbaek [20] score (+) on hit perfect score timing, target size (+) Mulder et al [23] steering (driving sim) Rakita et al [29] steering (robotic arm) Rogers et al [31] extra points no points free points (no for goals for enemy player input) Smeddinck et al [4] slower fall speed, smaller balance loss on hit Vicencio-Moreira [37] area cursor (+), target lock target gravity sticky targets, bullet magnetism Table 1. Overview of employed action-level PAMs, increases are marked (+), decreases (-)…”
Section: Framework Of Action-level Pamsmentioning
confidence: 99%
“…Our results showed that 59.1% of our participants expressed that they rarely, if ever, check the content of release notes (the current industry practice), while 77.3% of our participants indicated they would prefer a previewing tool prior to purchase or deployment. As a result of poor mental model calibration tools, drivers may experience unexpected behaviors when on the road and therefore disengage the autopilot [28]. For example, researchers have found 10.5 hours of YouTube videos that record how autopilot has surprised drivers [4].…”
Section: Introductionmentioning
confidence: 99%